Milk processing and collection in Romania: An analysis across regions - Mariana Grodea (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 7th Edition of the International Symposium, November 2016, Bucharest, 2016)
The excessive farm fragmentation and the permanent decrease of dairy cow herds resulted in the diminution of the milk quantities delivered to processing from 1.8 million tons (43.4%) in 1990 to 1.1 million tons in 2014 (24.3%). The results of the analysis reveal that the milk collection centers authorized for intra-community trade do not operate in all the counties of the country. Nationwide, there are 902 centers, out of which 39% are found in the counties Botoðsani (215) and Mureðs (139). By contrast, the milk processing factories authorized for intra-community trade operate in almost all the counties (except for Mehedin÷ti county), 171 in total, the highest concentration being found in the counties Suceava (17), Constanðta (14) and Mureðs (12). The support to the milk sector is one of the priority directions of the new NRDP 2014-2020, through investments in the modernization of dairy farms and milk collection centers and distribution of finished products.
Keywords: Q10; Q13; Q19; 330; processing; milk collection